2010
DOI: 10.1136/jme.2009.033977
|View full text |Cite
|
Sign up to set email alerts
|

A patient and relative centred evaluation of treatment escalation plans: a replacement for the do-not-resuscitate process

Abstract: The Treatment Escalation Plan (TEP) was introduced into our trust in an attempt to improve patient involvement and experience of their treatment in hospital and to embrace and clarify a wider remit of treatment options than the Do Not Resuscitate (DNR) order currently offers. Our experience suggests that the patient and family are rarely engaged in DNR discussions. This is acutely relevant considering that the Mental Capacity Act (MCA) now obliges these discussions to take place. The TEP is a form that the doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…2123 In the current study, survival to discharge fell steeply with increasing neurologic disability at admission, from 39.6% for those with no major disability, 22.6% for those with moderate disability, 19.6% for those with severe disability and 6% for those in a coma or vegetative state. Among patients with baseline neurological deficits, the number of co-existing medical diagnoses did not change survival outcomes.…”
Section: Discussionmentioning
confidence: 40%
“…2123 In the current study, survival to discharge fell steeply with increasing neurologic disability at admission, from 39.6% for those with no major disability, 22.6% for those with moderate disability, 19.6% for those with severe disability and 6% for those in a coma or vegetative state. Among patients with baseline neurological deficits, the number of co-existing medical diagnoses did not change survival outcomes.…”
Section: Discussionmentioning
confidence: 40%
“…There was no such reduction in harms in patients with DNACPR orders on other wards during the same time-period, or for patients remaining for CPR, suggesting that the change we observed was due to the use of the UFTO, and not seasonal variation or hospital-wide safety improvements. Accepting that we were looking at a group of patients who have worse outcomes than the standard hospital population, it is worth noting that no previous study of any initiative aimed at improving patient safety (as measured with the GTT) has shown such a profound effect, and that while alternative approaches to recording DNACPR decisions have previously been developed they have not been rigorously assessed for impact upon patient care [18], [19].…”
Section: Discussionmentioning
confidence: 99%
“…While alternative approaches have previously been developed, [18], [19] they have not been applied universally, nor their impact on patient care assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, Treatment Escalation Plans are replacing DNACPR orders in some hospitals (Mercer, ), offering a wider range of treatment options, with an emphasis on how the patient will be managed, rather than what interventions will be with‐held. Initial evaluation suggests that they are positively viewed by patients and families (Obolensky et al ., ). Nevertheless, recent reports published by the UK National Confidential Enquiry into Patient Outcome and Death (NCEPOD) highlight inadequacies in end‐of‐life care: the review of services for children's surgery identified that ‘end of life care was absent for those for whom it may have been appropriate’ (NCEPOD, , p.71), whilst the recent review into cardiac arrest outcomes (NCEPOD, ) highlighted a lack of discussion about resuscitation options between health care professional and patient, highlighting the need for a major culture shift.…”
mentioning
confidence: 97%